Determinação simultânea de ftalatos em lodo de esgoto utilizando a extração sólido-líquido com purificação em baixa temperatura - Najara Glenda Frota Pereira (2016)
A sensitive analytical method was optimized for simultaneous extraction and determination of five phthalate esters, dimethylphthalate (DMP), dibutylphthalate (DBP), butylbenzylphthalate (BBP), diethylylphthalate (DEHP) and dnoctylphthalate (DNOP) in sewage sludge samples. Were optimized the criteria of method execution: water volume, extractive phase, freezing time, agitation mode and additional clean up for extraction using the SLE-LTP technique. The optimized method consisted of 4 mL of water, extractive phase composed of ACN / ACT, 90 min of freezing, 30 sec of vortexing and without additional clean up. The experimental results demonstrated extraction percentages of 102.64 ± 4.56 to 139.08 ± 10.8 for all phthalates. The chromatographic condition and the selection of ions for gas chromatography coupled to mass spectrometry (GC-MS) were also evaluated for simultaneous determination of the analytes in a single injection. The quantification of the concentration of the phthalates DBP and DEHP present in the initial sample was performed by the standard addition method. The LQ for the DMP, BBP and DNOP compounds was 40 g kg-1. The method was successfully applied to detect the five phthalates and to quantify the occurrence of three phthalates in sewage sludge from six cities of Minas Gerais.